Knowledge, attitudes, practice, and perceived barriers toward evidence-based practice among Palestinian nurses in intensive care units - Zeina Dabak; Dalia Toqan; Malakeh. Z. Malak; Rasmieh Al-Amer; Ahmad Ayed (BMC Nursing)
Abstract Background Evidence-based practice (EBP) implementation can improve healthcare safety and patient outcomes. The significant challenge for intensive care nurses is providing safe and evidence-based care to patients with complex illnesses who are at high risk of complications and death. This study aimed to assess the knowledge, attitudes, and practice of EBP, and the perceived barriers to EBP implementation among nurses in intensive care units (ICUs) in the North West Bank hospitals. Methods A cross-sectional descriptive correlational design was employed, with 154 registered nurses from governmental and private ICU hospitals in the North West Bank of Palestine participating. Data were collected using a self-reported questionnaire from December 2022 to July 2023. Results The findings revealed that the attitudes mean was (M = 5.1 SD ± 1.1), followed by knowledge (M = 4.8, SD ± 1.4), and practice (M = 4.6, SD ± 1.2). The main barriers to EBP were insufficient time to find research reports (M = 3.5, SD ± 1.0) and inadequate time at work to implement changes in own practice (M = 3.4, SD ± 0.8). A correlation was found between knowledge, attitudes, and practice of EBP with Levels of education (t = 2.68, p < 0.01; t = 2.98, p < 0.01; t = 4.83, p < 0.01, respectively), attending EBP courses (t = 4.30, p < 0.01; t = 20.0, p < 0.01; t = 4.30, p < 0.01, respectively), and age (r = 0.159, p < 0.05; r = 0.234, p < 0.01; r = 0.289 p < 0.01, respectively). In contrast, the experience was associated with the practice of EBP (t = 1.77, p < 0.05). Conclusion The intensive care nurses had positive knowledge, attitudes, and practice of EBP, while attitudes were more favorable than knowledge and practice. Thus, the findings can assist policymakers and hospital administration in developing appropriate interventions and strategies, such as effective continuing education and developing and implementing a hospital-wide EBP culture to improve nurses’ knowledge and practice of EBP.